2004
DOI: 10.1021/ie034146t
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction and Gasification of Cellulose with Na2CO3 and Ni in Subcritical Water at 350 °C

Abstract: Cellulose decomposition without catalyst, liquefaction with Na2CO3, and gasification with Ni were studied in an autoclave and in a 50-nL microreactor (diamond anvil cell; DAC) coupled with optical and infrared microcopy in subcritical water up to 350 °C. Solid residue was the main product for noncatalytic decomposition of cellulose, which took place mostly under heterogeneous conditions at slow heating rates (0.18 °C/s). Homogeneous conditions could be achieved at a high heating rate of 2.2 °C/s, and solid res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 51 publications
9
94
1
2
Order By: Relevance
“…Previous researchers reported that one of the most important types of compounds present in bio-oil obtained from hydrothermal liquefaction of biomass were weak acids such as acetic acid, formic acid, and levulinic acid [5,6,9]. The acids were mainly produced from the decomposition of hemicelluloses and cellulose.…”
Section: Investigation Of Presumed Hydrothermal Liquefaction Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researchers reported that one of the most important types of compounds present in bio-oil obtained from hydrothermal liquefaction of biomass were weak acids such as acetic acid, formic acid, and levulinic acid [5,6,9]. The acids were mainly produced from the decomposition of hemicelluloses and cellulose.…”
Section: Investigation Of Presumed Hydrothermal Liquefaction Mechanismmentioning
confidence: 99%
“…However, the use of environmentally friendly and low energy-intensive approaches is highly desired. Hot-compressed and super/subcritical water have been widely studied and developed as technologies for the conversion of biomass to clean fuel and valuable chemicals [6,7]. The main advantage of these technologies is that drying process is not required for the conversion of wet biomass, because the water contained in biomass served as solvent as well as reactant [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main product was then a solid residue (57 %) without any catalyst. [40] The reaction mechanisms for cellulose under homogeneous and heterogeneous conditions are quite different, and the scheme for these mechanisms proposed in the study by Kozinski and co-workers [40] is reported in Figure 9.…”
Section: Supercritical Water Gasification Of Cellulosementioning
confidence: 99%
“…Mechanisms of cellulose decomposition carried out in a homogeneous or a heterogeneous medium in subcritical water (adapted from Ref. [40]). …”
Section: Supercritical Water Gasification Towards Energetic Valorizationmentioning
confidence: 99%